International investment law and the global financial architecture - Tams, Christian J.; Schill, Stephan W., 1976-; Hoffman, Rainer; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2017)
The global crises of the early 21st century have tested the international financial architecture. In seeking to ensure stability, governments have regulated financial and capital markets. This in turn has implicated international investment law, which investors have invoked as a shield against debt restructuring, bail-ins or bail-outs. This book explores whether investment law should protect against such regulatory measures, including where these have the support of multilateral institutions. It considers where the line should be drawn between legitimate regulation and undue interference with investor rights and, equally importantly, who draws it. Across the diverse chapters herein, expert international scholars assess the key challenges facing decision makers, analyse arbitral and treaty practice and evaluate ways towards a balanced system of investment protection in the financial sector. In doing so, they offer a detailed analysis of the interaction between investment protection and financial regulation in fields such as sovereign debt restructuring and bank rescue measures. Combining high-level analysis with a detailed assessment of controversial legal issues, this book will provide guidance for both academics and legal practitioners working in international economic law, international arbitration, investment law, international banking and financial law.
Part I: Overarching perspectives -- 1. International investment law and the global financial architecture: identifying linkages, mapping interactions / Rainer Hofmann, Stephan Schill and Christian J. Tams -- 2. International investment arbitration and the global financial system: are they 'yin' and 'yang' or like oil and water? / Charles N. Brower and Alexandra Goetz-Charlier -- 3. International investment law and financial regulation: towards a deliberative approach / Matthias Goldmann -- Part II: Sovereign debt restructurings -- 4. Police powers of the state in sovereign debt restructurings / Hayk Kupelyants -- 5. Restructuring sovereign debt on the basis of collective action clauses / Christoph Ohler -- 6. Sovereign bond disputes before investment treaty tribunals: safeguarding the exercise of collective action clauses with a single-limb voting mechanism / Yanying Li -- 7. Bilateral investment treaties and the principles on responsible sovereign lending and borrowing: working together towards the provision of an international legal framework addressing sovereign debt issues? / Marie Sudreau -- Part III: Bank rescue measures -- 8. Bail-ins and international investment law: in and beyond Cyprus / Maurice Mendelson and Martins Paparinskis -- 9. Bank rescue measures under international investment law: what role for the principle of causation? / Anna de Luca -- 10. Bits and pieces: reflections on the relevance of bits in resolution-related litigation / Phoebus Athanassiou -- Part IV: Alternative claims and defences, new actors -- 11. Capital-flow management measures and international investment law - never the twain shall meet? / Prabhash Ranjan -- 12. Crisis as force majeure under international law and EU law: defending emergency measures, à la européenne, in investment arbitration under intra-EU BITs / Anastasios Gourgourinis -- 13. International financial institutions in investment law and arbitration / Michael Wolfgang Müller -- Index.
Contributors include: A. Asteriti, P. Athanassiou, C.N. Brower, A. De Luca, A. Goetz-Charlier, A. Gourgourinis, R. Hofmann, H. Kupelyants, Y. Li, M. Mendelson, M.W. Müller, M. Paparinskis, C. Ohler, P. Ranjan, S.W. Schill, M. Sudreau, C.J. Tams
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: zahraniční investice; foreign investments; e-knihy online; e-books online